Aplikasi MATLAB dan MySQL untuk Simulasi Jatuhan Radioaktif di Sekitar Fasilitas Nuklir - Supriyono Supriyono; Ause Labellapansa; Suwardi Suwardi (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
On places that have nuclear facilities, there was amount of stationer station to lookover of dropping radioactive. All of radioactive dropped spots may knew how big of entirelyradioactive as dropped with direct observing data’s from stationer station, we can usemeasurement with Finite Element Method. The measurement steps were to split area aroundof nuclear facility to square elements, where on of spot square element was a stationerstation. After dissertation process substituted into element equation and proceed withincorporation element equation, will resulted coefficient of Jacobi equation, droppedquantity, and area broad. Data needed was stationer station spots ordinate and large ofradioactive dropped. Data that run with database system on MySQL software and those datawas measure with element method with MATLAB software. Result on this research showedthat system may use for measuring dropped radioactive on each dropped spot on entirenuclear zone, equally.Kata kunci: fasilitas, nuklir, jatuhan, radioaktif, metode elemen hingga, matlab, mysql.